2008
DOI: 10.1002/pad.486
|View full text |Cite
|
Sign up to set email alerts
|

Implementing management tools in Turkish public hospitals: the impact of culture, politics and role status

Abstract: The government of Turkey has attempted to substantially improve the management of its public hospitals. However, an analysis of the performance of the quality certified hospitals finds only minor improvements. This study seeks to explain these disappointing results by interviewing 46 hospital managers and employees about the successes and failures of the management reform effort. The interviews suggest that traditional Turkish organisational culture often hinders attempts to decrease hierarchy, but, more posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
(15 reference statements)
0
6
1
Order By: Relevance
“…ISO 9001 directs managers to re-examine all their processes and identify any discrepancies between what employees are actually doing and what the documentation asks to be done. It focuses on processes rather than outcomes (Ozturk and Swiss, 2008). ISO 9001 encourages employees to demonstrate compliance with the procedures, rather than to strive for continuous improvement.…”
Section: Obstacles To Tqm Successmentioning
confidence: 99%
See 1 more Smart Citation
“…ISO 9001 directs managers to re-examine all their processes and identify any discrepancies between what employees are actually doing and what the documentation asks to be done. It focuses on processes rather than outcomes (Ozturk and Swiss, 2008). ISO 9001 encourages employees to demonstrate compliance with the procedures, rather than to strive for continuous improvement.…”
Section: Obstacles To Tqm Successmentioning
confidence: 99%
“…Employee IJHCQA 26,2 empowerment, commitment and involvement are key factors in the successful implementation of TQM and, were indeed included in previous TQM studies. Various studies have shown that human resources problems such as lack of employees' motivation and involvement in TQM activities, their low knowledge and experience about TQM implementation, changing employees' work habits, lack of team orientation, lack of linkages between employees' compensation and their performance and lack of time are human resource barriers in implementing TQM successfully in healthcare organisations (Alexander et al, 2007;Francois et al, 2003, Huq andMartin, 2000;Kozak et al, 2007;Mosadeghrad, 2005;Ozturk and Swiss, 2008;Withanachchi et al, 2007).…”
Section: Ijhcqa 262mentioning
confidence: 99%
“…This audit, as opposed to change, approach to OD was also evident in the discussion of initial OD exercises in a paper co-authored by one of the SNV officers (Dorji and Schreven, 2007). This problem may be exacerbated by the requirement that OD takes place on a regular basis -imposed OD can be problematic and may, in the end, be counterproductive (although there are supporters of directive OD such as Rao and Vijayalakshmi, 2000;Ozturk and Swiss, 2008).…”
Section: Od In Bhutan: Strategy and Implementationmentioning
confidence: 97%
“…Evidence of such studies in a developing country context is even more elusive. Rather, both theoretical and empirical studies have been more focussed on how transferable Western management techniques are to non-Western and developing countries (Blunt and Jones, 1997;McCourt and Ramgutty-Wong, 2003;O'Donnell and Turner, 2005;Zupan and Kase, 2005;Ozturk and Swiss, 2008) and on the application of strategic human resource management and change concepts to public sector organisations (Tompkins, 2002). Such literatures provide very useful guidance on the opportunities and challenges of using Western-inspired management tools in development; however we still seem to be missing the connection between the adoption of such techniques and the complex set of multi-level goals which these tools are enacted in pursuit of.…”
Section: Introductionmentioning
confidence: 99%
“…The failure of TQM in healthcare is due to the complexity of the healthcare systems, bureaucratic and highly departmentalised structure, multiple layers of authority, professional autonomy, and tensions between managers and professionals (5)(6)(7). Insufficient motivation for professionals to participate in TQM initiatives, the difficulties involved in evaluating the processes and outcomes, and a lack of market based competition were the major obstacles to TQM implementation in the health sector (8)(9)(10). Other barriers to successful TQM implementation in health sector were authoritative leadership, lack of top managers' support, lack of employees' involvement, lack of a plan for change, inadequate resources, lack of a quality-oriented culture, insufficient education and training, poor communication, and lack of customer focus (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%